Carboxylic acid stimulated silver shell isomerism in a triple core–shell Ag84 nanocluster. Issue 18 (9th April 2019) - Wang, Zhi; Sun, Hao-Tian; Kurmoo, Mohamedally; Liu, Qing-Yun; Zhuang, Gui-Lin; Zhao, Quan-Qin; Wang, Xing-Po; Tung, Chen-Ho; Sun, Di
Abstract : A unique triple core–shell Ag84 nanocluster displaying isomerism, which is controlled by different carboxylic acids and a one-way transformation (SD/Ag84a andSD/Ag84b ). Abstract : Isomerization is highly important in all aspects of science, yet it is rarely observed in nanoscience. Here, we synthesized a unique triple core–shell Ag84 nanocluster displaying isomerism, which is controlled by different carboxylic acids and a one-way transformation (SD/Ag84a →SD/Ag84b ). The innermost core is a rare Ag10 nanocluster which comprises an Ag6 octahedral unit as seen in face-centred cubic (fcc) silver metal and four capped Ag atoms. It templates two crescent-shaped polyoxometalate (W7 O26 ) 10− shells which are then enclosed in a shell of silver shaped as rugby balls. The organic ligands ( i PrS −, n PrCOO − and PhCOO − ) finally shield the metallic clusters. Due to slight differences in structure at two poles and the steric hindrance of n PrCOO − and PhCOO −, SD/Ag84a andSD/Ag84b adopt the shapes of flat-headed and cuspidal prolate spheres, respectively. Interestingly, PhCOOH is dominant over n PrCOOH whereby crystals ofSD/Ag84b were isolated if PhCOOH is added during the synthesis ofSD/Ag84a . This demonstrates that PhCOOH not only alters the organic coats but also induces metal shell re-organization. This work reveals carboxylate-controlled skeletal isomerism in silver nanoclusters for the first time, thus deepening the understanding of silver nanocluster assembly, flexibility and reactivity.